DEPENDENCE OF LIVING WEIGHT ON THE FEEDING AND STORAGE OF IMPORTED (Academicia Globe: Inderscience Research, 2021)
In fully revealing the genetic potential of cattle in productivity as the influence result of hereditary and paratypical factors, if the genetic factor depends on the type, breed, pedigree of the animal, that paratypical factors are related to feeding and storage conditions, the breeding and selection work effectiveness, and the activity type by live weight of cows in the experimental groups.